Successful school leadership preparation and development - Sanzo, Karen L.; Myran, Steve; Normore, Anthony H. (Bingley, U.K. : Emerald, 2012)
This book will feature lessons learned about the successful implementation of leadership program preparation and development programs that are grant-funded by the United States Department of Education through the School Leadership Program. Each chapter will highlight one or more practices that have been identified as a best practice by the literature and detail how the program implemented the practice(s). It is clear from the literature what should be done to prepare aspiring and current leaders (i.e. mentoring, in-depth internships, partnerships) but what is not clear is how to do this. This book will do exactly that with real-life experiences in the implementation of these practices (including successes, challenges, etc.). These will be authentic examples from the field about how practitioners have addressed challenges in implemented successful activities such as coaching, the internship, evaluating projects, and forging partnerships with preparation entities.
ch. 1. Leadership preparation program evaluation : experiences and insights / Ann ODoherty, Margaret Terry Orr -- ch. 2. The power of institutional partnership in the development of turn around school leaders / Stephen H. Davis, Ronald J. Leon, Miriam L. Fultz -- ch. 3. Planning, changing, and leading a community of professional practice : lessons learned from an innovative urban school leaders preparation program in southern California / Antonia Issa Lahera, Anthony H. Normore -- ch. 4. Creating and sustaining dynamic university/school district partnerships for the preparation of learning-centered school leaders / Betty V. Fry, David Collins, Edward Iwanicki -- ch. 5. A rigorous recruitment and selection process of the University of Texas at Austin principalship program / Mark A. Gooden, Richard Gonzales -- ch. 7. Learning-centered leadership development program for practicing and aspiring principals / Jianping Shen, Van E. Cooley -- ch. 7. Preparing and supporting principals in rural South Dakota schools / Jeanne Cowan, Janet Hensley -- ch. 8. Re-designing lessons, re-envisioning principals : developing entrepreneurial school leadership / Kristy Hebert ... [et al.] -- ch. 9. Learning from the evolution of a university-district partnership / Karen L. Sanzo, Steve Myran -- ch. 10. The rural Alaska principal preparation and support program : a comprehensive approach to strengthening school leadership in rural Alaska / J. Kelly Tonsmeire ... [et al.] -- ch. 11. Accelerating leadership excellence : NYC leadership academy's school leadership coaching model / Tierney Temple Fairchild -- ch. 12. The integration of practical, cognitive, and moral apprenticeships for leadership learning : the evolution and initial impact of full-time internships / Susan Korach, Maureen Sanders.
Includes indexes.
Print version record
Keywords: Education -- Leadership; Education -- Administration -- General; Organization & management of education; Schools; School administrators -- Training of -- United States; Educational leadership -- Study and teaching -- United States; School management and organization -- Study and teaching -- United States